A new device for ultrasound-guided peripheral venous access. Issue 3 (May 2019) - Brugioni, Lucio; Barchetti, Marco; Tazzioli, Giovanni; Gelmini, Roberta; Girardis, Massimo; Bianchini, Marcello; Schepis, Filippo; Nicolini, Matteo; Pinelli, Giovanni; Martella, Pietro; Barozzi, Marco; Mori, Francesca; et al.
Background: In patients with difficult peripheral venous access, alternative techniques require expertise and are invasive, expensive, and prone to serious adverse events. This brought us to designing a new venous catheter (JLB® Deltamed, Inc.) for the cannulation of medium and large bore veins; it is echogenic, and available in different lengths (60 / 70 / 80 mm) and Gauges (14 / 16 / 17 / 18). Methods: We led a multi-center observational convenience sampling study to evaluate safety and effectiveness of JLB. Data was collected from June 2015 to February 2018. Inclusion criteria were age ⩾ 18, difficulty in obtaining superficial venous access in the veins of the arm, need for rapid infusion, or patient's preference. Results: We enrolled 1000 patients, mean age 66.8 years. In total, 951 (95.1%) had the device placed in internal jugular vein, 28 in basilic or cephalic vein, 15 in femoral vein, 5 in axillary vein (infra-clavicular tract), and 1 in the external jugular vein. The procedure was performed by attending physicians or emergency medicine residents under US guidance. Mean procedure time (from disinfection to securing) was approximately 240 s. Mean attempts number was 1.21. Early complications (<24 h) occurred in four patients, consisting in two soft tissue hematoma, one phlebitis, and one atrial tachyarrhythmia. No major complications (such as pneumothorax) were reported. Mean indwelling time was 168 h (7 days); early occlusion/dislocation occurred in four cases. Conclusion: According to preliminary data, the application of JLB appears to be safe, cost-effective, and rapid to place bedside.